Biochar Derived from Sugarcane Bagasse for Adsorption of Anionic and Cationic Dyes - Maria Alaide de Oliveira; Elibe Silva Souza; Davi Vieira Correia; Bráulio Silva Barros; Joanna Kulesza Barros (Materials Research)
In this study, biochar‑derived adsorbent was prepared by pyrolysis of sugarcane bagasse using the activation step with KOH and applied for dye removal. The structural characterization methods, X‑ray diffraction, infrared, and Raman spectroscopy showed that the material is purely carbonaceous. Scanning Electron Microscopy revealed that the material has a rough and irregular morphology with cavities of various sizes. The material showed good efficiency for methylene blue (MB) (96.6%) and methyl orange (MO) (95.1%) removal. The experimental data fit well with a pseudo-second-order model. Based on the Langmuir isotherm, the material exhibits good maximum adsorption capacity for removing MB (8.20 mg/g). The material was able to remove MB at different pH values (3-11), with good removal efficiency (above 60%). The biochar could remove MB in up to 5 cycles with good removal efficiency. The biochar obtained from sugarcane is a potential material for removing dyes from wastewater via adsorption.